Salt, blood pressure and cardiovascular risk: what is the most adequate preventive strategy? A Swiss perspective - Burnier, Michel; Wuerzner, Gregoire; Bochud, Murielle (Frontiers in Physiology, 2015)
Among the various strategies to reduce the incidence of non-communicable diseases reduction of sodium intake in the general population has been recognized as one of the most cost-effective mean because of its potential impact on the development of hypertension and cardiovascular diseases. Yet, this strategic health recommendation of the WHO and many other international organizations is far from being universally accepted. Indeed, there are still several unresolved scientific and epidemiological questions that maintain an ongoing debate. Thus what is the adequate low level of sodium intake to recommend to the general population and whether national strategies should be oriented to the overall population or only to higher risk fractions of the population such as salt-sensitive patients are still discussed. In this paper, we shall review the recent results of the literature regarding salt, blood pressure and cardiovascular risk and we present the recommendations recently proposed by a group of experts of Switzerland. The propositions of the participating medical societies are to encourage national health authorities to continue their discussion with the food industry in order to reduce the sodium intake of food products with a target of mean salt intake of 5-6 grams per day in the population. Moreover, all initiatives to increase the information on the effect of salt on health and on the salt content of food are supported.